Sosialisasi dengan Tema Peta Jalan Sukses Strategi Orang Tua dalam Mengembangkan Potensi Anak Usia Dini PAUD Nur Hidayah Cibomo Desa Bendung Kecamatan Kasemen: Pengabdian - Dira Rizki Amalia; Siti Muawanah; Riski Wulandari; Munawaroh (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
This community service activity aims to provide parents with understanding and skills in designing effective strategies to develop the potential of early childhood, especially at PAUD Nur Hidayah Cibomo, Bendung Village, Kasemen District. Through a socialization with the theme